2009
DOI: 10.1073/pnas.0813286106
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a functional protein complex of netrin-4, laminin γ1 chain, and integrin α6β1 in mouse neural stem cells

Abstract: Molecular and cellular interactions coordinating the origin and fate of neural stem cells (NSCs) in the adult brain are far from being understood. We present a protein complex that controls proliferation and migration of adult NSCs destined for the mouse olfactory bulb (OB). Combinatorial selection based on phage display technology revealed a previously unrecognized complex between the soluble protein netrin-4 and laminin ␥1 subunit that in turn activates an ␣6␤1 integrin-mediated signaling pathway in NSCs. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 43 publications
6
93
0
2
Order By: Relevance
“…Integrins, a family of cell adhesion receptors, are up-regulated in stem cells and are believed to support cell stemness by mediating adhesive interactions between stem cells and their niches (60). Integrin ␣6, a subunit for two laminin receptors, is also highly expressed in several types of stem cells, including subventricular neural stem cells (61,62), and facilitates neural stem cell adherence to endothelial cells in the perivascular niche (62). Integrin ␣6 has also been identified as a marker for cancer stem cells, including GSCs (48,53).…”
Section: Discussionmentioning
confidence: 99%
“…Integrins, a family of cell adhesion receptors, are up-regulated in stem cells and are believed to support cell stemness by mediating adhesive interactions between stem cells and their niches (60). Integrin ␣6, a subunit for two laminin receptors, is also highly expressed in several types of stem cells, including subventricular neural stem cells (61,62), and facilitates neural stem cell adherence to endothelial cells in the perivascular niche (62). Integrin ␣6 has also been identified as a marker for cancer stem cells, including GSCs (48,53).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these factors interact with integrin signaling during cell proliferation [64], adhesion and migration [65][66][67], neurite outgrowth, and growth cone guidance [68][69][70]. It is thus possible that other extracellular cues execute their roles through modulating integrin signaling directly or indirectly.…”
Section: Laminin/integrin Signaling In Microtubule Assemblymentioning
confidence: 99%
“…The lamininintegrin-mediated interaction also contributes to the development of the NSC niche and the maintenance of its integrity (Loulier et al, 2009). In addition, netrin 4 secreted by glial fibrillary acidic protein (GFAP)-positive astrocytes and laminin secreted by NSCs themselves can activate the 61 integrin-mediated signaling pathway to control NSC proliferation (Staquicini et al, 2009). Integrins can also promote NSC self-renewal by facilitating Notch and EGFR signaling (Campos et al, 2006), and integrins have recently been shown to regulate thrombopoietin-mediated HSC maintenance (Umemoto et al, 2012).…”
Section: Controlling Stem Cell Self-renewal Via Signalingmentioning
confidence: 99%